Peacemaking and reconciliation: the contribution of African indigenous religious women in KwaZulu-Natal, South Africa - Phiri, Isabel A. (Journal of Theology for Southern Africa, 2005)
In South Africa peacemaking and reconciliation have tended to be associated with male leaders dialoguing with government leaders to find peaceful solutions about internal or external conflicts. This article attempts to show that African women's peace-making efforts are overlooked because they occur mainly at community level. It focuses on African indigenous religious women who have religious health assets, which are used at a local level for peace making and reconciliation for the well-being of African communities. Material is drawn from periods both during and after apartheid in South Africa to show what these women were doing and thinking in terms of peacemaking and reconciliation. It uses oral history methodology in collecting information from fifteen African Indigenous women healers, and discusses how African Indigenous beliefs and practices co-exist peacefully with Christianity in the lives of the women interviewed. The article concludes with a challenge to take seriously the contribution of African Indigenous religious women in South Africa to peace-making and reconciliation efforts.
Keywords: Christianity and African religions; KwaZulu-Natal (South Africa); Leadership; Religious – African religions; Peace movement; Reconciliation; Women – South Africa